2009
DOI: 10.1038/cdd.2008.197
|View full text |Cite
|
Sign up to set email alerts
|

IRX-2, a novel immunotherapeutic, protects human T cells from tumor-induced cell death

Abstract: IRX-2 is a cytokine-based biologic agent that has the potential to enhance antitumor immune responses. We investigated whether IRX-2 can protect T cells from tumor-induced apoptosis. Tumor-derived microvesicles (MV) expressing FasL were purified from supernatants of tumor cells and incubated with activated CD8+ T cells. MV induced significant CD8+ T-cell apoptosis, as evidenced by Annexin binding (64.4±6.4%), caspase activation (58.1±7.6%), a loss of mitochondrial membrane potential (82.9±3.9%) and DNA fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 29 publications
4
95
0
1
Order By: Relevance
“…Thus, TEX induce apoptosis of activated CD8 + T cells by engaging extrinsic and intrinsic apoptosis pathways (60). The in vitro data discussed above are consistent with reports of similar changes in the expression of the pro-or antiapoptotic family members in circulating T cells of patients with cancer (61,63).…”
Section: Functional Attributes Of Texsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, TEX induce apoptosis of activated CD8 + T cells by engaging extrinsic and intrinsic apoptosis pathways (60). The in vitro data discussed above are consistent with reports of similar changes in the expression of the pro-or antiapoptotic family members in circulating T cells of patients with cancer (61,63).…”
Section: Functional Attributes Of Texsupporting
confidence: 87%
“…TEX-mediated signals leading to apoptosis of activated CD8 + T cells were associated with early membrane changes (i.e., annexin V binding) in target cells, caspase 3 cleavage, cytochrome C release from mitochondria, loss of the mitochondrial membrane potential (MMP), and, finally, DNA fragmentation (60). The PI3K/AKT pathway is a key target of TEX in activated CD8 + T cells (60,61). Recently, phosphatase and tensin homolog (PTEN), which regulates PI3K/AKT signaling, was found to be a component of the TEX cargo and to mediate phosphatase activity in recipient cells (62).…”
Section: Functional Attributes Of Texmentioning
confidence: 99%
“…We found that TEX produced by tumor cells may exert direct or indirect effects on human immune cells. TEX induce apoptosis of activated anti-tumor effector T cells [28,29]; TEX inhibit functions necessary for sustaining anti-tumor responses such as activation, proliferation and cytotoxicity [28]; TEX interfere with normal differentiation of immune cells [26,30]; TEX polarize immune cells to tumor-promoting phenotypes and regulate mobilization of immune cells to the tumor [31,32]. Indirectly, TEX expand proliferation of Treg and myeloid-derived suppressor cells (MDSC) and up-regulate suppressor activity of these cells thus contributing to tumor-induced immune suppression and the tumor immune escape [33,34].…”
Section: Inhibition Of Anti-tumor Immune Responses By Texmentioning
confidence: 99%
“…These data suggest that TEX induce apoptosis in activated CD8+ T cells by engaging extrinsic as well as intrinsic apoptotic cascades. Further, the PI3K/AKT pathway is the key target for TEX in activated CD8+ T cells: dramatic, time-dependent AKT dephosphorylation and concomitant decreases in expression levels of BCL-2, BCL-xL and MCL-1 accompanied by an increase in levels of pro-apoptotic BAX were observed in these cells during co-incubation with TEX [29]. …”
Section: Mechanisms Of Tex-mediated Suppression In T Cellsmentioning
confidence: 99%
“…Exosome cargos include proteins, such as enzymes, cytokines, growth factors, lipids and nucleic acids, including mRNA or microRNA and ncRNA [7577]. It has been shown that tumor cells are avid producers of exosomes, which play a role in many aspects of tumor progression including: degradation of the extracellular matrix [78]; angiogenesis [79]; suppression of immune cell functions [56,80,81] and drug resistance [82]. …”
Section: Tumor-derived Exosomes (Tex)mentioning
confidence: 99%